PROFIL PENCAPAIAN KETERAMPILAN PROSES SAINS DAN PENINGKATAN KEMAMPUANKOGNITIF SISWA KELAS X DALAM PEMBELAJARAN FISIKA DENGAN BANTUAN LKS INQUIRY ACTIVITY BERBASIS MODEL PEMBELAJARAN CURIOUS NOTE PROGRAM (CNP) - Fatimah Primadian; Agus Yulianto; Budi Astuti (Phenomenon : Jurnal Pendidikan MIPA, 2018)
This study aims to determine the profile of achievement of students 'science process skills and students' cognitive abilities improvement in physics learning with the help of LKS Inquiry Activity based on CNP learning model. The study design used was a One Group Pretest-Posttest Design. The subject of this research is students of class X SMA Negeri 7 Yogyakarta amounting to 32 students. The data were collected by using test instruments in the form of pretest-posttest, LKS Inquiry Activity based on CNP learning model, and student response questionnaire. The profile of students 'science skill achievement can be determined from the scores criteria scores 5. The results obtained after using LKS Inquiry Activity based on CNP learning model that is the achievement profile of students' science process skill in Finding Out Question, Discussion, And Determination And Study Related Theory is included in the good category with a score of 4.00, 4.11 and 3.53, respectively. For the Inquiry Activity skill, it is categorized as excellent with a score of 4.50. Meanwhile, students' cognitive abilities increased with an average score of 4.32 with a good category. Students' responses to LKS Inquiry Activity based on the CNP learning model earned a grade of 3.57 in either category. It indicates that LKS Inquiry Activity based on CNP learning model can know the profile of the achievement of science process skill.